The Use of Youtube Podcast to Improve Student Speaking Skills - Sudrajat, Awal Muhammad Nur; Febriani, R. Bunga (Journal of English Education Program (JEEP), 2025)
This study aims to improve students' speaking skills by using YouTube podcasts and students' perceptions of the use of YouTube podcasts in speaking skills. In conducting this research, the author used a case study to collect data from the participants. The participants were an English teacher and twenty eleventh-grade students at a boarding school in Tasikmalaya. There were two instruments used by the author in conducting this research, namely observation and interviews. The results of this study showed a positive perception through the strategies used by the teacher and helped the students in increasing their confidence in practicing speaking. Based on the research findings, it is suggested that teachers can use YouTube podcasts to improve speaking skills for senior high school students. Moreover, this strategy not only improves students' speaking skills but also students' knowledge and imagination through YouTube podcasts and interaction strategies in the classroom. In addition, this study also suggests that English teachers use YouTube podcasts as a strategy to improve students' speaking skills. In addition, the students felt that learning by using YouTube podcasts can help them to improve their speaking skills. In addition, it makes them more motivated and enjoy learning in class. For future researchers, this study provides a wide opportunity to make more perfect research in the same field with different interests.